‘Between party and parliament: The roles of parliamentary party group leaders in partitocratic Belgium’: PhD by Benjamin de Vet (Ghent University) - Louwerse, Tom (Politics of the Low Countries, 2025)
The study of legislative behaviour has recently taken flight, whereas role theory seems to have taken a back seat. Seminal works of Eulau and Wahlke and Searing are still discussed today, but perhaps their primary focus on describing parliamentary roles rather than explaining role variation affects the attractiveness of role theory to contemporary researchers. Benjamin de Vet’s Between Party and Parliament offers at least two promising contributions to this area of research. First, he extends the use of role theory from members of parliament in general to parliamentary party group (PPG) leaders specifically. His in-depth analysis of their roles, using data from 68 in-depth interviews, demonstrates a rich understanding of how PPG leaders themselves and their party colleagues conceive of PPG leaders’ roles. Second, de Vet does not only develop a descriptive typology of these roles, but also applies qualitative comparative analysis (QCA) to analyse potential explanations of role variance.